PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V SD NEGERI 106836 LIMAU MANIS - Marbun, Dinda Natalia Br; Asnita Hasibuan; Heka Maya Sari Sembiring; Regina Sipayung; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Quantum Teaching learning model on student learning outcomes in the subject of Science in grade V of Elementary School 106836 Limau Manis. This type of research is quantitative research using experimental methods. The type of sample used is purposive sampling. The research sample used was 34 students of class VB. To determine the initial abilities of students, researchers conducted a Pre-Test with an average value of 53.67 which is included in the less category. The results of the Post-Test have an increase from the results of the Pre-Test with an average value of 84.52 with a very good category. Based on the results of the study, it shows that there is an influence of the Quantum Teaching learning model on the learning outcomes of class VB students of Elementary School 106836 Limau Manis. The results of this study indicate that the results of the correlation test can be seen in the correlation coefficient value of 0.623, meaning that r hitung (0.623) > r tabel (0.396) means Ha is accepted. Sothere is a strong influence between the Quantum Teaching learning model on student learning outcomes. It can also be seen from the results of the t-test where t hitung > t tabel, namely 4.510 > 1.690, thus stating that Ha is accepted. This shows a significant positive influence of the use of the Quantum Teaching learning model on learning outcomes in the subject of science for grade V at SD Negeri 106836 Limau Manis in the 2024/2025 academic year.